THE USE OF FOLKLORE TO IMPROVE THE STUDENT’S READING COMPERHANSION OF NARRATIVE TEXT - Tria Miranda; Lustina Anggraini; Filya Filya (PT. Intelek Cendikiawan Nusantara, 2024)
This research paper explores the use of folklore to enhance students' reading comprehension of narrative texts in English language learning. The study highlights the challenges faced by Indonesian students in mastering English, with low proficiency levels reported in the EF English Proficiency Index. The paper proposes the